Contemporary and Future Secondary Copper Reserves of Southeast Asian Countries - Thi Van Le; Sebastien Michael Rene Dente; Seiji Hashimoto (Recycling)
This study employed dynamic material flow analysis (MFA) and mass balance principles to examine copper flows in Indonesia, Malaysia, the Philippines, Thailand, and Vietnam from 1960 to 2020, with projections extending to 2050 using five shared socioeconomic pathway (SSP) scenarios. We applied the secondary resources classification framework to assess secondary copper resources and their recoverability in these countries. The results indicated that total copper stocks across these countries would continue to rise, with Indonesia’s copper stock projected to reach around 5000–12,000 kt by 2050, the highest among the five nations. In 2022, Malaysia had the highest per capita copper stock at 100 kg/person, although all countries were expected to remain below the per capita stock levels seen in major copper-consuming developed countries by 2050. Copper demand was projected to increase by 118–238 kt annually from 2023 to 2050, leading to a significant rise in end-of-life copper scrap. By 2050, secondary copper reserves in Indonesia were estimated to reach 4096 kt, with similar growth trends observed in other countries (3898 kt in Thailand, 3290 kt in Vietnam, 3096 kt in Malaysia, and 2564 kt in the Philippines). This highlights both the potential for resource recovery and the need for improved waste management. If recycling rates increase to 80–90%, secondary reserves could meet up to 42–65% of the copper demand in 2050. However, current recycling rates remain well below this potential, underscoring the urgent need for better waste management systems. This study emphasizes the balance between economic development and resource sustainability, offering critical insights for policymakers to improve recycling efficiency and reduce reliance on primary copper sources.